The executive Sarawak Government’s administration machinery / Nadrawina Isnin, Abang Yusuf Abang Spawi and Nursuria Mahrif - Isnin, Nadrawina; Abang Spawi, Abang Yusuf; Mahrif, Nursuria (2004)
This study reports on the government’s administration of Sarawak from the executive aspect. It is a study to understand the historical development and its modus operandi in the context of Sarawak. This is to provide new and updated information of the Sarawak government’s administration. As an administrator, the state government of Sarawak plays an important role to ensure policies are implemented and procedures followed. With regards to this, it aims to understand the basis of democracy in Sarawak based on the role the government plays through the implementation of policies. It shows that Sarawak is undergoing a vast change in the development based on a positive development policy. Having a strong and reliable government through its ruling party, it is found that there is a commitment and dedication of the government’s functions. This shows the capability of the state government of Sarawak to carry out development projects for the benefit of the society as a whole. The good governance of Sarawak is much attributed to the successful of the government to overcome challenges and stood up to the critiques.